Hubungan Potensi Indra, Akal, Dan Kalbu Dalam Al-Qur’an Menurut Para Mufassir - Sawaluddin Siregar (Pascasarjana UIN ANTASARI Banjarmasin, 2020)
In the Qur'an the letter an-Nahl verse 78, Allah indicates that the potential (hearing, sight, and heart) that has been granted needs to be optimally and integrated developed. Because with that potential he can learn from the environment, nature, and the community where he lives with the hope of becoming a complete adult human being. This research was designed in the form of library research or Library research that uses various sources of literature as a data source that relates to the thinking of a character who at a certain time, cultural conditions, the community at that time, along with documents, then the methodologically used approach is interpretation. Based on the explanations of the three potentials, they clearly appear to have a close relationship, and support each other, if one thing does not function properly, it will not produce a good response. Indra's potential, aql, and Kalbu have strong, inseparable relationships. The position of each potential and that drives the potential, resulting in the application of the effects of stimuli received by the senses which are then transfected into oak and the brain sends data to the heart and heart which integrates the case, resulting in action